VIBRATIONS OF THIN WINGS IN THE SEPARATED FLOW. CALCULATION AND EXPERIMENT - V. V. Ovchinnikov; Yu. V. Petrov (Научный вестник МГТУ ГА, 2016)
The results of computational and experimental study of thin wings flutter in separated and unseparated flow are presented. The effect of flutter suppressing in the presence of separation is found.